On-Farm Phenotypic and Morphological Characterization of Indigenous Chicken Populations in Gambella Region, Ethiopia - Bekele , Getachew; Goshu, Gebeyehu; Melesse, Aberra; Esatu, Wondmeneh; Dessie, Tadelle (International Journal of Poultry Science, 2020)
Background and Objective: The first phase of characterization of indigenous chicken involves the identification of population based on morphological descriptors that can also provide useful information on the suitability of breeds for selection. The study was conducted to characterize on-farm phenotypic and morphological features of indigenous chicken population in selected districts of Gambella regional state, Ethiopia. Materials and Methods: Both purposive and random sampling techniques were used to collect the data and assessed through a semi-structured questionnaire survey. Data on visual appraisal and linear body measurements were obtained from a total of 600 matured local chickens of both sexes taken from 384 households. Linear body measurements were analyzed using the generalized linear model procedures. Results: The majority of the male chickens possessed red plumage color (30.5%) and most of chicken populations had single combs (80.84%), plain head shape (96.5%), yellow shanks color (85.34%) and feathered Shanks (1.67%). The male chickens were generally heavier (1.38 kg) than the female chickens (1.16 kg). The mean for body length, shank length, keel bone length, wingspan, wattle length, comb length and comb height of the cocks were 39.76, 10.19, 11.66, 65.77, 3.44, 5.28 and 2.15 cm, respectively. Conclusion: Variation in qualitative traits such as plumage color, feather distribution, comb type, earlobe color, shank feather, head shape and shank color indigenous chickens were evaluated in the study areas. The dominant plumage colour of the cocks was red followed by black and Gebsima (greyish with varying mixture) with other colors and in hens brown color followed by black and white.